1999
DOI: 10.1074/jbc.274.46.33114
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Human NF-κB p52 Transcription Factor with DNA-PNA Hybrids Mimicking the NF-κB Binding Sites of the Human Immunodeficiency Virus Type 1 Promoter

Abstract: We determined whether peptide nucleic acids (PNAs) are able to interact with NF-B p52 transcription factor. The binding of NF-B p52 to DNA-DNA, DNA-PNA, PNA-DNA, and PNA-PNA hybrid molecules carrying the NF-B binding sites of human immunodeficiency type 1 long terminal repeat was studied by (i) biospecific interaction analysis (BIA) using surface plasmon resonance technology, (ii) electrophoretic mobility shift, (iii) DNase I footprinting, and (iv) UV cross-linking assays. Our results demonstrate that NF-B p52… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
61
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 54 publications
3
61
0
Order By: Relevance
“…In a recent study, we proposed PNAs as alternative reagents in experiments aimed at the control of gene expression involving the decoy approach (20). In PNAs, the pseudopeptide backbone is composed of N-(2-aminoethyl)glycine units (27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent study, we proposed PNAs as alternative reagents in experiments aimed at the control of gene expression involving the decoy approach (20). In PNAs, the pseudopeptide backbone is composed of N-(2-aminoethyl)glycine units (27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that NF-B p52 is able to bind to both DNA/DNA and DNA/PNA hybrids mimicking the NF-B target sites present in the HIV-1 LTR. On the contrary, low binding of NF-B p52 to PNA/PNA hybrids was found (20). We have also reported a conformational study to explain these binding data using a molecular dynamics approach.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…This results in an attenuation of the authentic interactions of trans-factors with their cis-elements. 11 PNAs are able to interact with mRNA independently of the RNA secondary structure. Studies on the mechanisms of antisense activity have demonstrated that PNA inhibits expression differently than antisense oligonucleotides acting through RNase-H mediated degradation of the mRNA -oligonucleotide hybrid.…”
Section: Antisense and Antigene Applicationsmentioning
confidence: 99%